2023
DOI: 10.1111/1475-6773.14191
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neighborhoods and friendships on interracial anxiety among medical students and residents: A report from the medical student CHANGES study

Abstract: Objective: To examine the experience of interracial anxiety among health professionals and how it may affect the quality of their interactions with patients from racially marginalized populations. We explored the influence of prior interracial exposure-specifically through childhood neighborhoods, college student bodies, and friend groups-on interracial anxiety among medical students and residents. We also examined whether levels of interracial anxiety change from medical school through residency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Plaisime et al analyzed data from a retrospective longitudinal study of physicians in training surveyed over the course of medical school and residency, and explored potential associations between non‐Black students' interracial contact prior to medical school—the racial compositions of their childhood neighborhoods, college campuses, and friend groups—and their interracial anxiety with Black patients. 19 The authors found that medical students and residents from less diverse neighborhoods and with less diverse friend groups had more interracial anxiety. These findings highlight another pathway by which racial segregation can lead to inequities in health and health care and the importance of considering racial socialization in selecting and training a healthcare workforce equipped with the skills to address those inequities.…”
Section: Interpersonal Racismmentioning
confidence: 98%
“…Plaisime et al analyzed data from a retrospective longitudinal study of physicians in training surveyed over the course of medical school and residency, and explored potential associations between non‐Black students' interracial contact prior to medical school—the racial compositions of their childhood neighborhoods, college campuses, and friend groups—and their interracial anxiety with Black patients. 19 The authors found that medical students and residents from less diverse neighborhoods and with less diverse friend groups had more interracial anxiety. These findings highlight another pathway by which racial segregation can lead to inequities in health and health care and the importance of considering racial socialization in selecting and training a healthcare workforce equipped with the skills to address those inequities.…”
Section: Interpersonal Racismmentioning
confidence: 98%